The Model Reader in Cemil Kavukçu’s Başkasının Rüyaları - Fatih İkiz (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
While readers and their role have long been excluded by literary critics in explaining and interpreting a text, these have started to gain ground, especially in post-structuralist studies. The Italian literary critic, theorist, and semiotician Umberto Eco, who studies the processes by which readers make sense of a text and how the text guides readers, has developed the concept of the model reader. He explains the beginning, the process, and the completion of reading a work of literature through the metaphor of the fictional woods. According to Eco, the model reader, upon starting to read a text, enters the woods and lingers by following the directions the model author leaves in the text; the reader turns back or goes forward, takes different paths, and leaves the forest after reaching the deep meaning of the narrative. Eco (2013) details the concept of the model reader in his Six Walks in the Fictional Woods, and this concept will be applied to collection of short stories titled Başkasının Rüyaları [Someone Else’s Dreams], by Cemil Kavukçu (2011) who is regarded as an essential representative of contemporary Turkish literature in the field of short stories. This work from Kavukçu consists of nine short stories and can be considered as chapters of a book that complete each other because of the intensively woven interconnections and interrelations between the stories. For this reason, the corpus of the study consists of all the stories in Kavukçu’s work. This article mainly uses the concept of the model reader as developed by Eco in order to analyze issues such as how the reader captures these connections, under the light of which textual and narrative clues the reader establishes relationships, and what role the reader has.